(12 x 5) +{8-4+3-5 x 8 +(2+8÷4)}√9-5
valeriaporrastoscano:
el reusltado seria 17 asi me salio en la calculadora
Respuestas
Respuesta dada por:
10
Respuesta:
La respuesta es 136.
Explicación paso a paso: (60)+[27]x raiz de 9-5=60+27 por 3-5=60+81-5= 141-5=136
Respuesta dada por:
26
Respuesta:
(12 x 5) +{8-4+3-5 x 8 +(2+8÷4)}√9-5
60 + {8-4+3-5 x 8 +(4)}√9-5
60 + {8-4+3-5 x 8 +4}√9-5
60 + {-29}√9-5
60 - 29 √4 = 2
Preguntas similares
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años